Analysis of the stress distribution in the soft composite sphere - Koh, Bryan Zhanrong (Nanyang Technological University, 2020)
In recent history, bioengineering has never taken on such an essential and crucial in our medical advancements. The usage of hydrogels in drug deliveries have been made much more prominent due to the composites’ increased pH sensitivity and ionic strength. Moreover, hydrogels are also able to protect the deliverables such as medicinal drugs, peptides and various proteins from the external environment. This paper will discuss about the various research and development that has been done in hydrogels, such as the different classifications, the types of release mechanisms and the structures. It will also discuss briefly on the previous works which focused on constant dilatation in multilayer spheres, leading up to the primary focus of this project: dilatation in first-order linear elasticity. The first part details the investigation and discussion on displacement and stress trends in a two-layer hydrogel sphere with dissimilar materials. The second portion focuses on the two-layer sphere in which the first layer is hollow. Further analysis about the numerical results will be mentioned before the conclusion on any future possible research in this field, with emphasis on the second-order dilatation in hydrogel spheres.